Effects of solution conditions on the self-assembly of the chaperone protein DNAJB6b - Carlsson, Andreas; Maier, Victoria; Fricke, Celia; Pálmadóttir, Tinna; André, Ingemar ; 0000-0002-4753-8233; Olsson, Ulf ; 0000-0003-2200-1605; Linse, Sara (Communications Chemistry, 2025)
Chaperone proteins are essential for maintaining proteostasis. Their main role is to assist with the folding of other proteins and to prevent the aggregation of misfolded proteins. The molecular chaperone DNAJB6b efficiently suppresses amyloid formation of several peptides. This activity may rely on the same physicochemical properties as those driving chaperone self-assembly into large micellar-like oligomers. We have therefore undertaken a systematic study of DNAJB6b’s self-assembly under different solution conditions. Using complementary biophysical techniques, we probe variations in aggregation number distribution and hydrodynamic radius, upon variation of pH, temperature, ionic strength, or anions across the Hofmeister series. We find that DNAJB6b maintains its propensity to self-assemble under all solution conditions examined. The size and compactness of the micelles change upon unfolding of the C-terminal domain, although a folded C-terminal domain does not drive micelle formation, which can likely be ascribed to hydrophobic interactions in the linker region. Mass photometry reveals that monomers of DNAJB6b coexist at equilibrium with the micelles. Furthermore, the free energy barrier for micelle dissociation into monomers was estimated by measuring dissociation rate constants at different temperatures. (Figure presented.)